2013
DOI: 10.1021/ic4015465
|View full text |Cite
|
Sign up to set email alerts
|

Three New Mixed-Alkali- and Alkaline-Earth-Metal Borates: From 1D Chain to 2D Layer to 3D Framework

Abstract: Three new mixed-metal borates, K4Ba2[B14O20(OH)10]·3H2O (1), LiSr2[B10O16(OH)3] (2), and LiBa[B9O15] (3), have been made under hydro(solvo)thermal conditions and characterized by means of IR, UV-vis-near-IR, thermogravimetric analysis, powder X-ray diffraction, and single-crystal X-ray diffraction, respectively. 1 is a 1D chain constructed from B14O21(OH)10(10-) cluster units, 2 is of a 2D layer with nine-membered-ring windows built up of B10O19(OH)3(9-) cluster units, while 3 exhibits a 3D framework with 12-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…With respect to borates, they reveal a wide optical transparency window, varied acentric structure types, high laser damage thresholds, and large polarizabilities. As such, several commercial borate-based NLO materials have been developed, including β-BaB 2 O 4 (β-BBO), LiB 3 O 5 (LBO), KBe 2 BO 3 F 2 (KBBF), etc. Among borates, alkali and alkaline earth metals are the preferred alternative elements for designing borate-based NLO materials, mainly because those selected cations are free of d–d or f–f electronic transitions, which is beneficial for good transparency in the UV and even the deep-UV spectral region. , As a result, a variety of mixed alkali and/or alkaline earth metal borates, BaAlBO 3 F 2 , Na 2 CsBe 6 B 5 O 15 , Li 4 Sr­(BO 3 ) 2 , K 3 B 6 O 10 X (X = Br, Cl), , etc., have been frequently reported as front-line candidates for UV or deep-UV NLO materials.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to borates, they reveal a wide optical transparency window, varied acentric structure types, high laser damage thresholds, and large polarizabilities. As such, several commercial borate-based NLO materials have been developed, including β-BaB 2 O 4 (β-BBO), LiB 3 O 5 (LBO), KBe 2 BO 3 F 2 (KBBF), etc. Among borates, alkali and alkaline earth metals are the preferred alternative elements for designing borate-based NLO materials, mainly because those selected cations are free of d–d or f–f electronic transitions, which is beneficial for good transparency in the UV and even the deep-UV spectral region. , As a result, a variety of mixed alkali and/or alkaline earth metal borates, BaAlBO 3 F 2 , Na 2 CsBe 6 B 5 O 15 , Li 4 Sr­(BO 3 ) 2 , K 3 B 6 O 10 X (X = Br, Cl), , etc., have been frequently reported as front-line candidates for UV or deep-UV NLO materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have revealed that the introduction of cations with large ionic radii, such as alkali and alkaline‐earth metals, is a feasible way to obtain pure borates with B−O anion‐templated open‐framework structures. For example, the 12‐membered boron ring channels in LiBaB 9 O 15 are built from [B 3 O 7 ] 5− clusters. Additionally, in our previous studies, we synthesized two isostructural open‐framework borates, Na 8 MB 21 O 36 (M=Rb and Cs), with two different types of large channels (24‐ and 26‐membered rings), which present the first examples of the [B 21 O 36 ] 9− FBB in borates …”
Section: Introductionmentioning
confidence: 99%
“…A new borogermanate, SU‐16, with intersecting 12‐ and 8‐membered rings channels has also been successfully synthesized under mild hydrothermal conditions and shows a novel zeolite framework topology with coordination sequences different from those of other zeolite frameworks. Additionally, pure borates with B−O anion‐templated open‐framework configurations also show rich structural diversity . Many investigations have revealed that the introduction of cations with large ionic radii, such as alkali and alkaline‐earth metals, is a feasible way to obtain pure borates with B−O anion‐templated open‐framework structures.…”
Section: Introductionmentioning
confidence: 99%
“…14–17 These diverse cluster units normally arrange in an orderly manner in the crystal lattice and interact with each other through covalent bonds or H-bonds to make up discrete clusters, 1D chains, 2D layers and 3D frameworks. 18–21…”
Section: Introductionmentioning
confidence: 99%